MEMBANGUN HIGH ORDER THINKING (HOT) PESERTA DIDIK MELALUI CONTEXTUAL TEACHING LEARNING (CTL) DI MADRASAH - Ilham, Moch Wahid (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2017)
This paper describes the efforts of teachers in building High Order Thinking (HOT) Learners through Contextual Teaching Learning (CTL). Education has always been the focus of various elements. Because the fate of a nation in the future depends heavily on the contribution of education. In the current learning process there are several gaps related to students' thinking assumptions. The majority of teachers understand his role as a disseminator rather than a student center; so the focus of education in schools is more on the factual knowledge. This then affects the student achievement scoring system more based on tests that are tested for low-level cognitive skills only. The existence of the Contextual Teaching Learning (CTL) learning model is expected to be a bridge to build High Order Thinking (HOT) learners who can ultimately make learners able to achieve High Order Thinking (HOT).